Variation in apparent diffusion coefficient measurements among women with locally advanced cervical cancer. Issue 3 (December 2015) - Gladwish, Adam P.; Han, Kathy; Foltz, Warren D.
Abstract: ADC variability from mixed data sets acquired from women with locally advanced cervical cancer appears to be predominantly of biologic origin. Intra-histology ADC variance was similar when pooled across technical factors. Inter-histology pooling increased ADC variance. Normalization to urine ADC improved intra-histology variance and receiver-operator curve test performance.